2008
DOI: 10.1590/s0100-69162008000200001
|View full text |Cite
|
Sign up to set email alerts
|

Uso de redes neurais artificiais na identificação de vocalização de suínos

Abstract: RESUMO:O bem-estar dos animais tem sido importante tópico de pesquisa na produção animal, principalmente no tocante às formas de sua avaliação. Na avaliação do bem-estar animal, a vocalização mostra-se como ferramenta interessante, por fornecer dados de forma não-invasiva, podendo também ser facilmente automatizada. O presente trabalho teve o objetivo de implementar algoritmo baseado em redes neurais artificiais, capaz de reconhecer vocalizações relacionadas com padrões indicativos de bem-estar. A pesquisa tev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 15 publications
0
13
0
10
Order By: Relevance
“…Neste contexto, as formas de se avaliar e quantificar o bem-estar do animal em ambiente de produção intensiva vem destacando-se como tema mais importante entre os pesquisadores da área (NÄÄS et al, 2008). Dentre os diferentes mecanismos de avaliação, despontam como metodologia inovadora de indicativo comportamental os registros e os estudos do nível de ruído de um grupo de animais e da vocalização.…”
Section: Introductionunclassified
“…Neste contexto, as formas de se avaliar e quantificar o bem-estar do animal em ambiente de produção intensiva vem destacando-se como tema mais importante entre os pesquisadores da área (NÄÄS et al, 2008). Dentre os diferentes mecanismos de avaliação, despontam como metodologia inovadora de indicativo comportamental os registros e os estudos do nível de ruído de um grupo de animais e da vocalização.…”
Section: Introductionunclassified
“…The found values were not significant probably due to the high value of variation coefficient for the group castrated without anesthesia (156.67) and the vale for those castrated using anesthesia (167.57). NÄÄS et al (2008) also found individual differences in vocalization of pigs submitted to a similar type of stress. In the results of the energy emitted during each phase of the castration procedure it is observed that, for the group castrated with anesthetic, the greatest energy expenditure occurred during the application of the anesthetics; as for the group castrated without anesthetic, the greatest expenditure happened during the castration surgery.…”
Section: Resultsmentioning
confidence: 71%
“…Among ways to audit animal welfare, there is monitoring of their behavior and social interactions (BAPTISTA et al, 2011;SPINKA, 2012), observation of health and rearing conditions (BAPTISTA et al, 2011;CALDARA et al, 2012), and monitoring of their vocalization expressed during production phases (MARX et al, 2003;SAMPAIO et al, 2007;NÄÄS et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Vocalization is an objective and noninvasive tool that may evidence lack of herd welfare based on the release of distinct vocal patterns (NÄÄS et al, 2008). MARX et al (2003) characterized different types of swine sounds and identified diverse parameters of emitted energy, frequency, and duration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation